Applications of Carbon in Rechargeable Electrochemical Power Sources: A Review - Jakub Lach; Kamil Wróbel; Justyna Wróbel; Andrzej Czerwiński (Energies, 2021)
Rechargeable power sources are an essential element of large-scale energy systems based on renewable energy sources. One of the major challenges in rechargeable battery research is the development of electrode materials with good performance and low cost. Carbon-based materials have a wide range of properties, high electrical conductivity, and overall stability during cycling, making them suitable materials for batteries, including stationary and large-scale systems. This review summarizes the latest progress on materials based on elemental carbon for modern rechargeable electrochemical power sources, such as commonly used lead–acid and lithium-ion batteries. Use of carbon in promising technologies (lithium–sulfur, sodium-ion batteries, and supercapacitors) is also described. Carbon is a key element leading to more efficient energy storage in these power sources. The applications, modifications, possible bio-sources, and basic properties of carbon materials, as well as recent developments, are described in detail. Carbon materials presented in the review include nanomaterials (e.g., nanotubes, graphene) and composite materials with metals and their compounds.